Effects of supplier's competitive factors on relationship performance and product recommendation in crop protection retail sector - Byungok Ahn; Bo-Young Kim; Jongpil Yu (Journal of Risk and Financial Management, 2022)
The changes in distribution channels of the crop protection industry are accelerating the influence of crop protection retailers on farmers' product purchase decisions. This study aims to identify the critical competitive factors; "product quality", "supply price", "brand awareness", "flexibility", and "promotion support"; of crop protection manufacturers. And it empirically analyzes effects of the critical factors on relationship performance and product recommendation of crop protection retailers. This research also examined the difference among these major factors according to the level of trust of crop protection companies as suppliers. Survey data were collected from 660 retailers by the crop protection distribution market in South Korea. As for the results, the five factors were defined as the crop protection suppliers' competitive factors. Supply price, promotion support, brand awareness, and flexibility had a positive (+) effect on relationship performance. Brand awareness, promotion support, product quality, and flexibility had a positive (+) effect on customer recommendation. Furthermore, supply price significantly affected relationship performance in a group with high trust, and promotion support significantly affected a group with low trust.
Keywords: 650; crop protection retail; competitive factor; relationship performance; product recommendation; trust